An Inquiry into Designing in Context using Generative Systems. (December 2014) - Abdelmohsen, Sherif M.
The use of generative systems has been widely investigated in the architectural design process through different procedures and levels of autonomy to generate form. The digression from abstract pre-existing notions of vocabulary and rules – even when resulting in emergent forms – to address complex real-world contexts is yet a challenging undertaking. This paper explores incorporating context in the process of designing using generative systems from ideation to fabrication, and explores the relationship between the emergent nature of generative design and the situated act of designing while using generative design tools. A course offered for 3 rd year architecture students at the Department of Architecture, Ain Shams University, Egypt, was designed for this purpose. 110 students employed systems including shape grammars, L-systems, fractals and cellular automata, to design and fabricate 8 group projects. A discussion around emergence and situatedness is presented, with special attention to the designing process from ideation to fabrication.